Simultaneous removal of ammonium and phosphate by alkaline-activated and lanthanum-impregnated zeolite. (December 2016) - He, Yinhai; Lin, Hai; Dong, Yingbo; Liu, Quanli; Wang, Liang
Abstract: Simultaneous ammonium and phosphate removal characteristics and mechanism, as well as the major influencing factors, such as pH, temperature and co-existing ions, onto NaOH-activated and lanthanum-impregnated zeolite (NLZ) were investigated. The phosphate adsorption increases from 0.2 mg g −1 for natural zeolite up to 8.96 mg g −1 for NLZ, while only a slight decrease on the ammonium adsorption capacity from 23.9 mg g −1 for NaOH-activated zeolite to 21.2 mg g −1 for NLZ was observed. The ammonium and phosphate adsorption showed little pH dependence in the range from pH 3 to 7, while it decreased sharply with the pH increased above pH 7. Adsorption of ammonium and phosphate could be well described by the pseudo-second-order model and the process was mainly governed by intra-particle diffusion. The Langmuir and Freundlich model can be acceptably applied to fit the experimental data, which suggested that adsorption was caused by both the monolayer and homogeneous coverage at specific and equal affinity sites available NLZ. The underlying mechanism for the specific adsorption of phosphate by NLZ was revealed with the aid of SEM-EDS, XPS, and FTIR analysis, and the formation of (LaO)(OH)PO2 was verified to be the dominant pathway for selective phosphate adsorption by lanthanum-impregnated zeolite. While the removal mechanism of ammonium could be well interpreted by SEM-EDS, FTIR and ICP analysis, and ion-exchange was expected to be the main removal process for ammonium. The results indicate that NLZ could efficiently and simultaneously remove low concentration of ammonium and phosphate from contaminated waters. Highlights: The adsorbent could remove low concentrations of ammonium and phosphate simultaneously and effectively. The absorption mechanism was investigated by means of SEM-EDS, FT-IR spectroscopy and XPS. Ion exchange and ligand complexation were the dominant mechanism for N&P removal, respectively.